1994
DOI: 10.1271/bbb.58.1496
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Xylanase A fromClostridium stercorariumF-9 and a RecombinantEscherichia coli

Abstract: Xylanase A encoded by the Clostridium stercorarium F-9 xynA gene was purified to homogeneity from a recombinant clone of Escherichia coli. The N-terminal amino acid sequence and molecular weight (54,000) estimated by SDS-PAGE of the purified enzyme were consistent with those deduced from the nucleotide sequence [Biosci. Biotech. Biochem., 57, 273-277 (1993)]. A xylanase was also purified to homogeneity from a culture supernatant of C. stercorarium F-9. Its N-terminal amino acid sequence, molecular weight, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These CBMs have been reported to bind to insoluble cellulose (Sakka et al , 1996). Restriction mapping of the xylanase‐encoding region of C. stercorarium (NCIB11754) indicated architecture identical to F‐9 Xyn11A , except for an ≈ 500 bp insertion near the 3′ end of the NCIB11754 Xyn11A region (Sakka et al , 1994). A 1300 bp fragment could be amplified from C. stercorarium (NCIB11754) genomic DNA using oligonucleotide primers designed to amplify the DNA encoding the tandem modules of F‐9 Xyn11A.…”
Section: Resultsmentioning
confidence: 99%
“…These CBMs have been reported to bind to insoluble cellulose (Sakka et al , 1996). Restriction mapping of the xylanase‐encoding region of C. stercorarium (NCIB11754) indicated architecture identical to F‐9 Xyn11A , except for an ≈ 500 bp insertion near the 3′ end of the NCIB11754 Xyn11A region (Sakka et al , 1994). A 1300 bp fragment could be amplified from C. stercorarium (NCIB11754) genomic DNA using oligonucleotide primers designed to amplify the DNA encoding the tandem modules of F‐9 Xyn11A.…”
Section: Resultsmentioning
confidence: 99%
“…Strains and Growth Conditions-The C. thermocellum strain F1 (15) and C. josui strain FERM (16) P-9684 were used for the isolation of genomic DNA and cellulosomal proteins. E. coli strains DH5␣, JM109, and BL21(DE3)RIL were obtained from Stratagene (La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Cellulosomal proteins isolated from C. josui (16) and C. thermocellum (15) were separated by SDS-PAGE in 13% gels, respectively, and transferred electrophoretically onto PVDF membranes (Bio-Rad, Hercules, CA) using an electroblotting apparatus, Compact Blot (ATTO, Tokyo, Japan). The membranes were blocked with PBS buffer (140 mM NaCl, 2.7 mM KCl, 1.5 mM KH 2 PO 4 , 8.1 mM Na 2 HPO 4 , pH 7.5) containing 0.5% (w/v) BSA (Fraction V; Sigma, St. Louis, MO) and 0.05% (v/v) Tween 20, followed by additional washing with PBS buffer containing 0.1% BSA and 0.05% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] Previously, we have cloned several genes related to xylan hydrolysis from C. stercorarium F-9,6) which had been isolated in this laboratory, and sequenced the xylA gene encoding a bifunctional protein with fJ-D-xylosidase and a-L-arabinofuranosidase activities 1 7) and the xynA gene encoding a family G xylanase (XynA).7) Immunological analysis has recently shown that the xynA gene was predominantly expressed as a xylanase gene in C. stercorarium F _9. 8 ) Although some other xylanase genes were also cloned from a type strain, NCIB, of C. stercorarium,9) these genes and the gene products have not yet been characterized in detail.…”
mentioning
confidence: 99%